Comparative study on pregnancy outcome of PIH, preterm labour and SGA among teenage primi mothers and non teenage primi mothers ( < 35 years) in Teaching Hospital Kandy - Weeasena, O.V.G.L (My University, 2010)
Teenage pregnancy could be defined as a pregnancy in a girl or a woman aged 10-19 years. Adolescent women face increased risks during pregnancyand childbirth. This research was designed to compare the pregnancy outcome between the teenage primi and non teenage primi mothers 35 years) in Sri Lanka with a view on educational and financial backgrounds. In the study sample mean birth weight of the babies of teenage mothers was 2.67kg (n= 121, SD=0.38). Mean birth weight of babies of non teenage mothers was 2.82kg (n=209, SD=0.050). On average teenage pregnant women delivered at 37.7 weeks (n=121, SD= =1.86) compared with non teenage who delivered at mean POA 38.04(n=209, SD=1.71) weeks. Applying non parametric test revealed an odds ratio of 1.206 ( 95 percent CI10.658- 2.210) which doesn’t show statistically significant difference in non teenage pregnancy compared with teenage pregnancies with regards to SGA.